Preferred Play Activities of Children with Autism Spectrum Disorder in Naturalistic Settings - Doody, PhD, Kathy Ralabate; Mertz, MBA, Jana (North American Journal of Medicine and Science, 2013)
Autism Spectrum Disorders (ASDs) are lifelong, neurobehavioral disorders that impact behavioral, social and communication skills. Introducing and designing appropriate play opportunities for children with ASD is of primary concern for educators, clinicians, and parents. The researchers set out to research the types of play most often preferred by children with autism spectrum disorders. Data collected in a children’s museum over a six month period resulted in a sample size of 1,506 observations for children with ASD. Data for the six months were aggregated for each of 20 different exhibits. Each of the top five exhibits preferred by children with ASD provided strong and distinct sensory feedback and featured cause/effect results or repetitive motions. Conversely, the five least popular exhibits for children with ASD were pretend play activities, and play activities which focused on arts/crafts. At a 95% confidence interval, eleven of the twenty exhibits showed a statistically significant difference for children with ASD than would be expected by a normal distribution. Of those eleven, six were preferred less than the expected average and five were preferred more than the expected average. Preliminary results of this research study support the researchers’ hypotheses that children with ASD prefer play activities with a strong sensory component and are far less likely to engage in activities involving pretend play. [N A J Med Sci. 2013;6(3):128-133. DOI: 10.7156/najms.2013.0603128]